Protocol for Determining Appropriate Adaptations for the International Weight Control Registry to Be Inclusive of People With Physical Disabilities. (14th June 2022) - Clina, Julianne; Sayer, Richard; Ferguson, Christine; Das, Sai; Hill, James; Roberts, Susan
Abstract: Objectives: People with physical disabilities (PWD) are at increased risk for developing obesity and weight-related comorbidities compared to the general population. While some barriers to weight loss (WL) are known, many behavioral, environmental, and psychological contributors to WL and weight loss maintenance (WLM) have yet to be identified for PWD. The International Weight Control Registry (IWCR) is a newly established longitudinal study that seeks to facilitate a deeper understanding of factors contributing to successes and challenges of weight management in diverse populations. However, the IWCR has not been systematically evaluated for its inclusiveness of PWD. The objective of this study is to identify suitable adaptations to the IWCR for it to be inclusive of PWD and identify unique contributors to WL and WLM for PWD. Methods: Adaptations will be identified using two expert panels: 1) a panel of inclusion specialists from the National Center on Health, Physical Activity & Disability and 2) a panel of PWD recruited from the Lakeshore Foundation in Birmingham, AL, (a fitness and advocacy organization for PWD) and previous participants in research including PWD. A Delphi method will be used to review questionnaires for inclusive language and to ensure the survey accurately represents issues relevant to PWD. PWD will then be recruited into the IWCR using the adapted questionnaire. Participants with and without disabilities will then be compared to determine components integral for WL and WLM between groups. Results: Study results will lead to an adapted version of the IWCR which will 1) identify psychological, environmental, and behavioral components leading to WL and WLM success for PWD and 2) evaluate differences between people with and without disabilities regarding barriers and facilitators to WL and WLM. Conclusions: The resulting registry is the first of its kind for PWD and will provide invaluable insight related to WL and WLM for PWD. These findings will help to inform obesity treatment for this population and will be incorporated into weight loss interventions for PWD in an effort to improve outcomes. Funding Sources: PhD training of Julianne Clina has been supported by the National Center on Health, Physical Activity & Disability.